Pemanfaatan Ulang Efluen Industri Pengolahan Susu Sebagai AIr Irigasi Untuk Tanaman Padi - Yani Suryani; Syamsul Bahri (Jurnal Irigasi, 2015)
Reuse of wastewater with no heavy-metal contains is potential in irrigation water supply, for example, effluent of milk processing industry. The aim of this study is to analyze the effect of milk industry effluent concentration to paddy growth (Oryza sativa L.). For case study, Ciherang variety with water-saving irrigation system scheme is used in an experimental plot with factorial design of 2 x 4. Several scenarios are applied: two treatments fertilization (with and without fertilization) and four variations of wastewater concentrations (0%, 50%, 75% and 100%). This study shows that the variation of wastewater concentrations with fertilization is not significantly affect the plant height, growth rate, number of tillers, and number of panicles. However it is significantly affect the wet grain weight and dry grain weight. The above result might be affected by the excessive nitrogen compound in the effluent, as the dry grain weight decreases to about 16% to 31%.